Does aging stop? - Mueller, Laurence D., 1951-; Rauser, Casandra L., 1974-; Rose, Michael R. (Michael Robertson), 1955- (Oxford : Oxford University Press, 2011)
Does Aging Stop? reveals the most paradoxical finding of recent aging research: the cessation of demographic aging. The authors show that aging stops at the level of the individual organism, and explain why evolution allows this. The implications of this counter-intuitive conclusion are profound, and aging research now needs to accept uncomfortable truths.
Title from home page (viewed on Sept. 5, 2011).
Also issued in print format.
Includes bibliographical references and index.
Keywords: Aging; Longevity; Mortality; Human evolution